Wideband radar cross‐section reduction of patch array antenna with miniaturised hexagonal loop frequency selective surface. Issue 9 (4th April 2016) - Zahir Joozdani, M.; Khalaj Amirhosseini, M.; Abdolali, A.
Abstract : Wideband radar cross‐section (RCS) reduction of a microstrip patch array antenna is proposed and investigated. The design is based on replacing the solid metal ground of the antenna with a frequency selective surface (FSS) consisted of miniaturised hexagonal loop elements. The stop band of the FSS is coincident with the antenna working frequency band which is from 3.3 to 3.4 GHz. The FSS acts as the ground plane in the stop band and is transparent to the incident waves in the other frequencies. Therefore, preserving the antenna propagation characteristics, wideband RCS reduction is achieved from 4 to 16.5 GHz for vertical and horizontal polarisations. It is shown that using this FSS has a negligible effect on the impedance bandwidth, pattern and gain of the antenna. Also, there is a good agreement between the simulation and measurement results.